DEVELOPMENT OF GLACIERS OF MOUNT ELBRUS AFTER THE LITTLE ICE AGE - E. A. Zolotarev; E. G. Kharkovets (Лëд и снег)
SummaryThe results of remote monitoring of the greatest inEuropemountain glaciation of Elbrus are covered for 120 years by instrumental survey (1887–2007) and lichenometric survey in 1986. The materials of stereoscopic digital photo survey of the whole glaciation with terrain resolution of2.5 metersproduced by space imaging system Cartosat-1 (IRS-P5) in 2007 were compared with the same year materials of phototheodolite survey of south glaciation slope (6 glaciers in total). Results of comparison showed that the data received from Cartosat-1 can be used for monitoring of glaciers with long enough interval of time between repeated surveys (from 10 years and more), and also is suitable for updating 1:25 000 topographic maps of mountain areas. The leading role of Dzhikiugankez plateau in changes was revealed. Over the last 50 years (1957–2007) the Dzhikiugankez share in change of the glaciation area as a whole has reached 45 %. The method of glacier dynamics research, based on digital technologies of image processing and assuming first of all visual deciphering of changes and in the second – measurement of parameters of changes is offered. The quantitative data of Elbrus glaciation reduction since the middle of the XIX century do not confirm the hypothesis of the global climate warming beginning just in the second half of XX century as a result of anthropogenic greenhouse gases effect. Contrarily in 1970s, many Elbrus glaciers advanced. Elbrus glaciation area reduction is occurring practically evenly through time and is alternated with short-term periods of stationary state and advance. These facts suggest that global climate warming, which alternated with short-term cooling periods, began after the end of the Little Ice Age and was most likely due to natural rather than anthropogenic causes.